2018
DOI: 10.1371/journal.ppat.1007008
|View full text |Cite
|
Sign up to set email alerts
|

Atrophy of skin-draining lymph nodes predisposes for impaired immune responses to secondary infection in mice with chronic intestinal nematode infection

Abstract: Intestinal nematodes suppress immune responses in the context of allergy, gut inflammation, secondary infection and vaccination. Several mechanisms have been proposed for this suppression including alterations in Th2 cell differentiation and increased Treg cell suppressive function. In this study, we show that chronic nematode infection leads to reduced peripheral responses to vaccination because of a generalized reduction in the available responsive lymphocyte pool. We found that superficial skin-draining lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(38 citation statements)
references
References 45 publications
2
36
0
Order By: Relevance
“…These divergent results may have several explanations such as the choice of model, infectious dose and the time of infection/s. While there are studies indicating systemic dissemination of both type 2 and regulatory responses after intestinal nematode infection, the effects are most evident when worm burdens are high and when the worm itself is in proximity to the secondary challenge …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These divergent results may have several explanations such as the choice of model, infectious dose and the time of infection/s. While there are studies indicating systemic dissemination of both type 2 and regulatory responses after intestinal nematode infection, the effects are most evident when worm burdens are high and when the worm itself is in proximity to the secondary challenge …”
Section: Discussionmentioning
confidence: 99%
“…20 In contrast, preexisting, acute Strongyloides ratti infection was found not to affect L major lesions in C57BL/6 mice despite hampered IFNγ levels in draining lymph nodes. 21 burdens are high [24][25][26][27] and when the worm itself is in proximity to the secondary challenge. 24 Lymphocytes are rare in healthy hepatic tissue of young SPF mice, 28 and as expected, the H. polygyrus infection alone did not affect expression of T cell-associated mRNAs in the liver.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,3 We and others have shown that worm infection can dampen immune responses to infection and vaccination in the skin. [4][5][6] Enhanced T helper-cell type 2 (TH2) and regulatory (TREG) responses are commonly suggested to drive the down-modulating effects of worms on subsequent immune responses. 2 Furthermore, we recently described how a chronic intestinal infection with the model worm pathogen Heligmosomoides polygyrus bakerii causes redistribution of circulating lymphocytes with accumulation of T cells in the mesenteric lymph nodes (mesLNs).…”
Section: Introductionmentioning
confidence: 99%